The roots of terrorism in Indonesia : from Darul Islam to Jema'ah Islamiyah - Solahudin (Cornell University Press, 2013)
Available for the first time in English, this groundbreaking book is an in-depth investigation of the development of jihadism from the earliest years of Indonesian independence in the late 1940s to the terrorist bombings of the past decade. The Indonesian journalist Solahudin shows with rare clarity that Indonesia's current struggle with terrorism has a long and complex history. The Roots of Terrorism in Indonesia is based on a remarkable array of documentary and oral sources, many of which have never before been publicly cited. Solahudin's rigorous account fills many gaps in our knowledge of jihadist groups, how they interacted with the state and events abroad, and why they at times resorted to extreme violence, such as the 2002 Bali bombings.